Research status of care experience and needs of family caregivers on gastrointestinal cancer patients (消化道肿瘤患者家庭照护者照护体验及需求研究现状) - SU Hongxia (苏红霞); YAN Wanhua (颜琬华) (Association of Integrative Nursing, 2023)
This paper reviewed the care experience and needs of family caregivers of patients with gastrointestinal cancer. The care experience of family caregivers of patients with gastrointestinal cancer mainly included three aspects: overloaded psychological load, decreased physiological function and limited social function; the needs of caregivers were mainly concentrated in the thirst for knowledge and skills in the care of patients with digestive tract cancer and the need for emotional and social support. The care support intervention measures for family caregivers of patients with digestive tract cancer are summarized, and it is suggested that nurses should pay attention to the negative psychological problems of the caregivers and give full play to their positive psychology. It can help caregivers strengthen the social support system and meet their psychological support needs, thereby improving the quality of their care. (本文综述消化道肿瘤患者家庭照护者照护体验及需求。消化道肿瘤患者家庭照护者照护体验主要包括心理负荷过重、生理功能减退及社交功能受限三个方面; 照护者需求主要集中表现为对消化道肿瘤患者照护知识和技能的渴求及情感和社会支持的需求。本文还梳理归纳了消化道肿瘤患者家庭照护者照护支持干预措施, 建议护理人员应重视照护者的消极心理问题, 发挥积极心理效应, 帮助照护者强化社会支持系统, 满足其心理支持需求, 从而提高照护质量。)